Instructions for authors - EMPRESARIAL, INQUIETUD (Unidad Editorial UPTC, 2015)
Inquietud Empresarial is a biannual scientific journal published by the Universidad Pedagógica y Tecnológica de Colombia’s School of Business Administration, Faculty of Economics and Administrative Sciences. It is oriented to academics, researchers, entrepreneurs, public and private officials, undergraduate and graduate students as a space for expression of thought of Management, Economics, Accounting andPolitical Sciences.